Comparison of butterfly communities between agroecosystems and dipterocarp forest in Khon Kaen province, Thailand - Chaianunporn, Kanokporn; Chaianunporn, Thotsapol (Agriculture and Natural Resources, 2022)
Importance of the work: Tropical forest areas in Southeast Asia have been extensively converted to other land uses. However, the impact of land conversion on butterfly diversity in this region has not been well studied. Objectives: To assess the impacts of land conversion on butterfly community assemblages by comparing butterfly diversity in dipterocarp forest and two agroecosystems Materials & Methods: Butterfly diversity was surveyed using belt transects and data on environmental factors that might be associated with butterfly distribution in the dipterocarp forest in Khok Phutaka, Khon Kaen province and in two adjacent agroecosystems (open areas and rubber tree plantations). Results: In total, 685 individual butterflies of 56 butterfly species were collected. The butterfly species richness and the Shannon-Wiener species diversity index were highest in the open areas, whereas the number of butterflies collected was highest in the rubber plantations. The dissimilarity of butterfly species assemblages was greatest between the dipterocarp forest and the other habitat types. The constrained correspondence analysis (CCA) revealed that six environmental factors (elevation, air temperature, litter depth, tree density, tree diversity and degree of human disturbance) were associated with butterfly species distribution. Elevation-human disturbance and tree diversity-litter depth gradients were observed in the ordination diagram biplot from the CCA. Main finding: Habitat conversion from dipterocarp forests to agroecosystems does not always lead to a decrease in butterfly diversity, but it does result in a change in butterfly community assemblages.